STEM Career Interest of Kazakhstani Middle and High School Students - Nursultan Japashov; Zhomart Naushabekov; Samat Ongarbayev; Adriana Postiglione; Nuri Balta (MDPI AG, 2022)
The aim of this study is to analyze secondary school students' career interests in STEM subjects. This survey-based quantitative research is provided to gain insight into the STEM career interests of 398 students (7-11 graders), in the Almaty region of the Kazakhstan Republic. Through parametric and non-parametric test analysis, the relationship between students' STEM career interest and their gender, their parents' occupation, parents' education, family size, school type, and school location were revealed. Results indicated that, on average, participant students showed positive interest in STEM careers. In particular, boys' and girls' responses were equally positive in many sub-scales of STEM. Additionally, great interest in STEM careers was shown by village students, whereas, for private school students who are living in the city, STEM career interests were the lowest in our sample. We also found that students' family size, parents' education, and occupation does not relate to students' STEM career interest. Implications for STEM education in Kazakhstan are further discussed in this study.